Outcomes in children evaluated but not transported by ambulance personnel: retrospective cohort study - Jelena Oulasvirta; Heli Salmi; Markku Kuisma; Eero Rahiala; Mitja Lääperi; Heini Harve-Rytsälä (BMJ Publishing Group, 2019)
Background Not all children with an out-of-hospital emergency medical contact are transported by ambulance to the emergency department (ED). Non-transport means that after on-scene evaluation and possible treatment, ambulance personnel may advise the patient to monitor the situation at home or may refer the patient to seek medical attention by other means of transport. As selecting the right patients for ambulance transport is critical for optimising patient safety and resource use, we studied outcomes in non-transported children to identify possible risk groups that could benefit from ambulance transport.Methods In a population-based retrospective cohort study of all children aged 0-15 years encountered but not transported by ambulance in Helsinki, Finland, between 1 January 2014 and 31 December 2016, we evaluated (1) 12-month mortality, (2) intensive care admissions, (3) unscheduled ED contacts within the following 96 hours after the non-transport decision and (4) the clinical status of the child on presentation to ED in the case of a secondary ED visit.Results Of all children encountered by out-of-hospital emergency medical services, 3579/7765 (46%) were not transported to ED by ambulance. There was no mortality or intensive care admissions related to the non-transport. The risk factors for an unscheduled secondary ED visit after a non-transport decision were young age (p=0.001), non-transport decision during the early morning hours (p<0.001) and certain dispatch codes, including 'dyspnoea' (p<0.001), 'vomiting/diarrhoea' (p=0.030) and 'mental illness' (p=0.019). We did not detect deterioration in patients' clinical presentation at ED traceable to non-transport decisions.Conclusions Not transporting all children by ambulance after an out-of-hospital emergency medical contact was not associated with deaths, intensive care admissions or significant deterioration in general condition in our study population and healthcare system. Special attention and a formal non-transport protocol are warranted in certain subgroups, including infants.